Development of Nutraceutical Ice Creams Using Flour Yellow Worm Larvae (Tenebrio molitor), Chia (Salvia hispanica), and Quinoa (Chenopodium quinoa) - Hernández Toxqui, Ana Gabriela; Ramírez Ramírez, Jazmín; Pino Moreno, José Manuel; Talamantes Gómez, José Moisés; Angeles Campos, Sergio C.; Ramírez Orejel, Juan Carlos (Frontiers in Veterinary Science, 2021)
Functional ice creams were developed by adding larvae of the insect Tenebrio molitor mixed with a seed (Salvia hispanica) and a pseudocereal (Chenopodium quinoa) to strawberry–cranberry ice cream. The objective was to increase micronutrients, macronutrients, and antioxidants, thus rendering the product a food complement. Four ice cream formulations were manufactured: the control strawberry–cranberry ice cream and three experimental mixtures, one of them with an addition of Tenebrio larvae (HT) and two others with a combination of Tenebrio larvae, chia (HTC), and quinoa (HTQ). The ice creams were submitted to proximate chemical analysis: mineral, fatty acid, vitamin, and one antioxidant (cyanidin 3 glucoside) determination. The strawberry–cranberry ice cream was used as a control formulation to evaluate if there were significant differences among nutrients, to which a Dunnett test with a critical value of α = 0.05% was applied. The three formulations that were studied showed a significant increase in the analyzed micronutrients and macronutrients compared to the control formulation. We observed increases of up to 62% in lipid content in the HTC formulation, while an increase of 41% in the protein content of the HT formulation was observed. We quantified an increase and enrichment of vitamins and minerals in the manufactured products, so that their nutritional value was significantly enhanced. In the determination of cyanidin 3 glucoside, we found that the formulation to which chia had been added showed an increase of 74% as compared to the control ice cream; this is important because anthocyanins are a group of flavonoids that stand out for their antioxidant and antimutagenic capabilities.